Strategic Variables in Sustainable Halal Tourism Village Economic Development: A MICMAC Analysis - Puspa Utami; Ahmad Syaifullah; Dolly Tanzil; Imam Asngari (CV. Era Digital Nusantara, 2026)
The novelty of this study lies in its methodological contribution through the application of MICMAC (Matrix of Cross-Impact Multiplication Applied to Classification) structural analysis in the context of sustainable halal tourism village development in Indonesia, an approach that remains rarely explored in previous halal tourism and rural development studies. Unlike conventional approaches such as descriptive analysis or SWOT analysis, this study employs MICMAC to systematically map the direct and indirect influence-dependence relationships among strategic variables within a complex rural tourism system. This study contributes by developing an integrated structural framework that simultaneously incorporates rural economic development, halal tourism principles, institutional governance, community participation, digitalization, environmental sustainability, and local cultural preservation. Through MICMAC analysis, the study is able to identify key driving variables, relay variables, dependent variables, and autonomous variables, thereby providing a more comprehensive understanding of the causal structure underlying sustainable halal tourism village development. Methodologically, this study demonstrates that MICMAC analysis can serve as an effective strategic policy tool for identifying priority intervention areas in complex village-based tourism systems. The findings provide a more systematic and evidence-based foundation for policymakers in designing phased and sustainable halal tourism village development strategies in Indonesia.